2016
DOI: 10.7717/peerj.1837
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of putative reference genes for quantitative real-time PCR normalization inLilium regaleduring development and under stress

Abstract: Normalization to reference genes is the most common method to avoid bias in real-time quantitative PCR (qPCR), which has been widely used for quantification of gene expression. Despite several studies on gene expression, Lilium, and particularly L. regale, has not been fully investigated regarding the evaluation of reference genes suitable for normalization. In this study, nine putative reference genes, namely 18S rRNA, ACT, BHLH, CLA, CYP, EF1, GAPDH, SAND and TIP41, were analyzed for accurate quantitative PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Similarly, ACT 11 was also not found to be a suitable reference gene for qRT-PCR studies in different tissues of poplar (Brunner et al, 2004). However, this gene was not the suitable reference gene under various developmental stages in rice (Pabuayon et al, 2016) and Lilium regale E.H. Wilson (Liu et al, 2016). In a previous report, ACT 7 was the most suitable reference gene for a developmental stage gene expression study in soybean ( Jian et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, ACT 11 was also not found to be a suitable reference gene for qRT-PCR studies in different tissues of poplar (Brunner et al, 2004). However, this gene was not the suitable reference gene under various developmental stages in rice (Pabuayon et al, 2016) and Lilium regale E.H. Wilson (Liu et al, 2016). In a previous report, ACT 7 was the most suitable reference gene for a developmental stage gene expression study in soybean ( Jian et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…In a previous report, ACT 7 was the most suitable reference gene for a developmental stage gene expression study in soybean ( Jian et al, 2008). However, this gene was not the suitable reference gene under various developmental stages in rice (Pabuayon et al, 2016) and Lilium regale E.H. Wilson (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a previous report, ACT 7 gene was the most suitable reference gene for developmental stage gene expression study in soybean (Jian et al 2008). However, this gene was not the suitable reference gene under various developmental stages in rice (Pabuayon et al 2016) and Lilium regale (Liu et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the earlier studies, GAPDH and ACT 7 genes were found to be suitable reference genes for qRT-PCR normalization under heat stress condition in Brachypodium distachyon (Hong et al 2008). In heat stress studies, the GAPDH gene was also found to be the most suitable reference gene in pigeonpea (Sinha et al 2015) and Lilium regale (Liu et al 2016) whereas this gene was not a suitable reference gene in cicer (Reddy et al 2016) and maize (Lin et al 2014). The ACT 7 gene was not the suitable reference gene in Caragana intermedia (Zhu et al 2013) for qRT-PCR studies in heat stress condition.…”
Section: Discussionmentioning
confidence: 99%